The Role Of Social Media To Strengthening Religious Moderation In Islamic Religious Education Students - Novita Fitrotun Ni'mah; Partono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study investigates the role of social media in strengthening religious moderation among students of Islamic Religious Education. Employing a literature review methodology, this research synthesizes existing scholarly works to analyze how social media platforms influence the understanding and practice of religious moderation among this specific student demographic. The study explores the potential of social media as a tool for disseminating moderate Islamic teachings, fostering interfaith dialogue, and countering extremist narratives. Furthermore, it examines the challenges and risks associated with social media use, such as the spread of intolerance and radical ideologies. The findings highlight the significant impact of social media on shaping students' religious perspectives and underscore the need for strategic approaches to harness its positive potential while mitigating its negative influences. The implications of this research suggest the importance of developing digital literacy and critical thinking skills among students, as well as designing effective online educational initiatives that promote religious moderation and inclusivity.